2022
DOI: 10.5864/d2022-016
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and opportunistic pathogens (OPs) in the built environment

Abstract: Table 1: Characteristics of selected opportunistic pathogens (OPs) of concern in Canada.Legionella spp. Description: Gram-negative bacteria, found in natural water systems and soils, have been detected in most large building water systems and some 10%-30% of home water systems in the United States. Legionella bacteria can be present in water storage containers, pipes, or outlets. Optimal growing conditions: Preference for warm water (e.g., 25-45 °C), high water age, low disinfectant residual, and often associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 74 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…L. pneumophila was detected in drinking water distribution systems only at temperatures greater than 18 • C [34]. In recent excellent reviews on the impact of climate change on opportunistic pathogens in water systems, O'Keeffe [35] and Blanc et al [36] provide evidence that increases in water temperature will increase the proliferation of Legionella spp., Mycobacterium spp., and other opportunistic pathogens. A pilot study by Calero-Preciado et al [37] demonstrated increases in opportunistic pathogens (M. avium, P. aeruginosa, Acanthamoeba, and S. maltophilia) in biofilm and water samples when water temperatures increased from 16 to 24 • C. O'Keeffe [35] notes that warmer temperatures would increase the use of cooling towers that could promote Legionella risk.…”
Section: Impact Of Climate Change On the Microbiology Of The Distribu...mentioning
confidence: 99%
See 3 more Smart Citations
“…L. pneumophila was detected in drinking water distribution systems only at temperatures greater than 18 • C [34]. In recent excellent reviews on the impact of climate change on opportunistic pathogens in water systems, O'Keeffe [35] and Blanc et al [36] provide evidence that increases in water temperature will increase the proliferation of Legionella spp., Mycobacterium spp., and other opportunistic pathogens. A pilot study by Calero-Preciado et al [37] demonstrated increases in opportunistic pathogens (M. avium, P. aeruginosa, Acanthamoeba, and S. maltophilia) in biofilm and water samples when water temperatures increased from 16 to 24 • C. O'Keeffe [35] notes that warmer temperatures would increase the use of cooling towers that could promote Legionella risk.…”
Section: Impact Of Climate Change On the Microbiology Of The Distribu...mentioning
confidence: 99%
“…In recent excellent reviews on the impact of climate change on opportunistic pathogens in water systems, O'Keeffe [35] and Blanc et al [36] provide evidence that increases in water temperature will increase the proliferation of Legionella spp., Mycobacterium spp., and other opportunistic pathogens. A pilot study by Calero-Preciado et al [37] demonstrated increases in opportunistic pathogens (M. avium, P. aeruginosa, Acanthamoeba, and S. maltophilia) in biofilm and water samples when water temperatures increased from 16 to 24 • C. O'Keeffe [35] notes that warmer temperatures would increase the use of cooling towers that could promote Legionella risk. Increased water conservation efforts due to climate change would accelerate the adoption of water efficient devices that could indirectly promote the growth of opportunistic pathogens through increased water age and decreased disinfectant residuals [35].…”
Section: Impact Of Climate Change On the Microbiology Of The Distribu...mentioning
confidence: 99%
See 2 more Smart Citations
“…According to some predictions, climate change will lead to more outbreaks of diseases caused by OPPPs, for example, due to greater use of air-conditioning systems, swimming pools, green infrastructure, etc. [54]. Therefore, new approaches and methods are needed in water disinfection and for the control and fight against OPPPs and their biofilms, and some of these approaches could be based on light-activated mechanisms and photoinactivation.…”
Section: Current Treatments In Water Disinfection and Eradication Of ...mentioning
confidence: 99%